PROSPECTIVE STUDY TO COMPARE INSULIN AND INSULIN ANALOGS IN TYPE II DIABETIC PATIENTS - Ks, Gireesha; M, Sumithra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To compare the safety and quality of life of insulin and insulin analogues in Type II Diabetic patients. Methods: 100 patients who are diagnosed with type – II diabetes milletus are taken.In these 50 patients are of insulin analogues and 50 patients are of conventional insulin The safety was based on number of hypoglycemic events.Data was collected by using the EQ-5D questionnaire and EQ Visual Analogue scale (EQ-VAS) to assess the quality of life from the patient. Result:The percentage of the patients who had hypoglycemic events in conventional insulin group is 54% (n=27) and insulin analogues group is 20% (n=10). Mean score points of QOL obtained by conventional insulin patients is 75.9 and by insulin analogues patients is 93.75 Conclusion: Insulin analogues group has low risk of hypoglycaemia when compared with the conventional insulin.The patient group who are in No problem category are found to have better QOL. The safety and QOL statistical differences constitute less likely among insulin and insulin analogues. The use of insulin analogues will continue to advance our efforts at improving diabetes care and treated related adverse outcomes can be reduced.